الاختبارات الموضوعية لبعض مقررات مرحلة البكالوريوس بكلية التربية لاعداد معلمات الابتدائي : دراسة تحليلية - المنصور، سناء بنت أحمد (جامعة الملك فيصل, 2011)
هدفت هذه الدراسة إلى تحليل أسئلة الاختبارات الموضوعية لمرحلة البكالوريوس بكلية التربية لإعداد معلمات الابتدائي بالرياض واستهدفت ثلاثة محاور رئيسة وهي أولاً: درجة تمثيل الاختبارات لمحتوى المقررات في ضوء الأهداف التدريسية الموثقة في الخطط الدراسية وفق آراء أصحاب الاختصاص، ثانياً: مدة توفر شروط كتابة أسئلة الاختبارات الموضوعية المستخدمة وفق معايير مراجعة الاختبارات الموضوعية في أدبيات التقويم التربوي وبشكل خاص المعايير المعدة من قبل وزارة التربية والتعليم في المملكة العربية السعودية، ثالثاً: التعرف على الفروق ذات الدلالة الإحصائية -إن وجدت- لنتائج التحليل بين الأقسام التعليمية في الكليات. وقد تكونت عينة الدراسة من 32 اختبار موضوعي من المجمع الأصلي 127 تمثل أقسام الكلية والمراحل الدراسية الأربعة. استخدمت الباحثة ثلاثة استمارات لرصد عملية التحليل شارك فيها 29 من المحللين من أعضاء هيئة التدريس من مختلف التخصصات، بحيث تم تحليل كل اختبار على حدة من قبل الباحثة وباحثين آخرين في مجال تخصص مادة الاختبار. ومن أبرز نتائج الدراسة تواضع مستوى تمثيل الاختبارات الموضوعية للأهداف السلوكية وافتقاره للشمول حيث بلغ مستوى التمثيل درجة "متوسط" في جميع أقسام الكلية، كما أظهرت النتائج فروق ذات دلالة إحصائية في توفر شروط بناء أسئلة الاختيار من متعدد بين اختبارات قسمي العلوم والرياضيات، ورياض الأطفال لصالح قسم العلوم والرياضيات. This study was aimed at analyzing objective test items that was employed as a testing measure in the final examination of undergraduate courses in the College of Education for Elementary Teachers Preparation in Riyadh. The study focused on three major areas, first: the degree of representation - in light of course syllabus - to course targets based on the opinion of experts in the subject matter ، second: the extent of compliance to construction terms of true-false and multiple choice test items in accordance with the criteria in the educational evaluation literature with special emphasis on criteria of test review drafted by the Ministry of Education in Saudi Arabia ، third: to find out -if there is any- statistical differences regarding analysis results between departments’ tests. Sample of the study constituted of 32 objective tests out of 127 representing college departments and four levels of schooling. The researcher used 3 forms to place test analysis ، 29 faculties from different \ disciplines participated in the process ، each test in the sample was analyzed separately by the researcher and two others specialized in the subject matter of the test. The most significant results of the study have shown that the degree of representation of tests items to course objectives was not inclusive and has gotten a ’’medium” rating. Study results have also shown statistical differences in compliance to multiple choice items construction terms between Science and Mathematics department and Kindergarten department for the benefit of the first one.
Keywords: معلمات الابتدائي -- اعداد المعلمين -- تقويم الأداء -- طالبات كليات التربية -- المناهج الدراسية -- الاختبارات الموضوعية -- التقويم التربوي -- السعودية